Functionalization of Eri silk and its union fabric using methanolic extract of Centella asiatica plant against Staphylococcus aureus - Rupjyoti Neog; Namrita Kola (Sustainable Chemistry for the Environment)
The present investigation aimed to evaluate Centella asiatica plant extract as a natural antibacterial finish in response to the growing need for sustainable alternatives in textile applications. Eri/Eri, Eri/Mulberry, and Eri/Cotton fabrics were treated using Centella asiatica extract by pad-dry method. Antibacterial efficacy against gram-positive bacteria Staphylococcus aureus (MTCC 7443) was evaluated using the AATCC 90–2011 method. The assessment encompassed fabric thickness, weight, crease recovery angle, tensile strength, stiffness, elongation, SEM analysis and whiteness index before and after finishing. The washing durability of the finish was determined using ISO 6330E after one and ten washing cycles. The finished fabrics exhibited a significant (p ≤ 0.05) zone of inhibition when compared with positive and negative controls affirming the effectiveness of the developed antibacterial finish. Characterization studies did not indicate drastic alterations in the physical properties after the application of the finishing treatment. Eri/Eri, Eri/Cotton and Eri/Mulberry fabric demonstrated a significant (p ≤ 0.05) laundering durability with recorded values of 11.83 mm, 11.56 mm and 8.67 mm respectively. The eco-friendly strategy offered by the present investigation demonstrated a viable solution for fulfilling the need of antibacterial fabric without sacrificing ecological or health concerns along with reported washing durability.